Comparative evaluation of remineralizing potential of four enamel remineralising agents using SEM-EDX – An in-vitro study - R. Raj (Journal of Oral Biology and Craniofacial Research)
Objective: Compare the remineralisation potential of four enamel remineralising agents on artificially demineralized enamel surface using Scanning electron microscopy- Energy dispersive x-ray. Materials and methods: 75 extracted maxillary and mandibular premolars coated with acid-resistant nail varnish, were stored in demineralising solution for 96 h to produce artificial caries lesions. The samples were divided into 5 groups (n = 15), Control (Demineralized- No treatment), Group I samples were treated with casein phosphoprotein-amorphous calcium phosphate (CPP-ACP), Group II with self-assembling peptide (SAP-14), Group III with tri-calcium phosphate (f-TCP) and Group IV with Bioactive glass (BAG), respectively. The pH cycling model was followed for 21 days. The samples were analysed via SEM-EDX (Carl Zeiss, Germany; Model: Merlin Compact) for qualitative assessment and quantitative analysis of calcium and phosphorous. The data were analysed for multiple group comparison using IBM SPSS version 20 with one-way ANOVA followed by a paired t-test. Results: Calcium/Phosphorous ratio of all experimental groups; Group 1(1.92 ± .17), Group 2 (1.98 ± .16), Group 3 (1.81 ± .03), Group 4 (1.75 ± .08) was statistically different (p < 0.0005) from Control; while there was no difference between Group I and Group II (p = 0.33). Conclusion: All experimental groups showed comparable remineralising potential. Even though no statistically significant difference is seen between Group I and Group II, after correlating with surface analysis it was concluded that Group II showed the greatest remineralising potential.